IOT BASED SMART AGRICULTURE WATER QUALITY MONITORING AND CONTROLLING SYSTEM - Dr. J. Deny, Mettupalli Venkatasivareddy, Ch. V. Saiteja, S. K. Shahul (Design Engineering, 2021)
Water is an essential element or liquid for the huge economic growth of the world. It widely used both the agriculture and non-agriculture productions. Whenever the population increases as well as water wastage are also increases and it builds a way en route for water scarcity. Water scarcity is a major disturbs to the total ecosystems. To diminish the water scarcity by the two major consequences such as improving land water and reducing the water wastage. The existing system lacks in sense the water pressure both the inlet and outlet. In that reducing water wastage, the proposed system is proposing a novel embedded sensors based IoT. It mainly focuses day to day life water wastage for the supplemented water resources. This IoT based water management system probes the water leakage using some precision sensors. It intimates and sends the message to the user about the leakage where it is founded. It has more advantages in both small and large scale pipeline systems. This proposed system mainly emphases reducing water leakage and it improved economical grade of the sectors.